(untitled) (Journal of Informatics Education and Research, 2024)
Non-verbal communication governs relationships and can enhance or even supplant verbal communication in numerous contexts. Diverse genders and cultures employ non-verbal communication distinctively, and these variations can influence the dynamics of interpersonal communication. Nonverbal communication can either hinder or facilitate efficient communication. Researchers indicate that non-verbal norms may vary depending on the context, with each context establishing its own rules. Neurodivergent individuals exhibit markedly different and distinct nonverbal communication behaviors. This pedagogical study explores various ways of nonverbal communication discussed by researchers in the past scientific literature that are beneficial to neurodivergent people who cannot speak.